Konseling Rational Emotive Behavior Therapy Islami dalam Menangani Perilaku Agresi dan Regulasi Emosi - Ilman Najah (AL-IBANAH, 2026)
High school outdoor club members are identified with extreme activities and are thought to tend to behave aggressively, even though they are tasked with preserving the environment. The aim of this research is to test the application of Islamic REBT Counseling in dealing with aggressive behavior and emotional regulation. This research is a qualitative research with a phenomenological design conducted on high school students who are members of KAP3LA at SMAN 24 Bandung with 10 informants. The analysis used is based on the Islamic REBT Counseling format with 4 aspects of aggressive behavior and 3 aspects of emotional regulation. Research is carried out by modifying irrational beliefs into rational beliefs. The results show that Islamic REBT Counseling is able to handle aggressive behavior and emotional regulation of KAP3LA member students at SMAN 24 Bandung.